Welcome :: Homework Help and Answers :: Mathskey.com

Recent Visits

  
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,267 questions

17,801 answers

1,438 comments

34,095 users

Solve the equation

0 votes

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13

asked Dec 29, 2017 in ALGEBRA 1 by anonymous

1 Answer

0 votes

The equation 

5(-3x - 2) - (x - 3)   =   - 4(4x + 5) + 13

- 15x - 10 - x + 3   =   - 16x - 20 + 13

- 16x - 7   =   - 16x - 7

-16x   =   -16x

0  =  0

Equation is valid for all values of x

answered Dec 29, 2017 by homeworkhelp Mentor

Related questions

asked Jun 17, 2014 in ALGEBRA 1 by anonymous
...